PENENTUAN KRITERIA KETERPADUAN TRANSPORTASI ANTARMODA DI BANDAR UDARA (Jurnal Penelitian Transportasi Darat, 2014)
ABSTRACTAir transport is one of the modes of transportation that provides great benefits include such a wide reach, travel time is relatively short, the rate was still accessible to the public as well as safe and comfortable. To be able to increase the passenger air transport services may be made by, the development of the air transport system in Indonesia is directed towards the realization of the integration of air transport services to various modes of transportation in order to create an integrated intermodal transportation. implementation of intermodal transport is to realize continuous passenger service, one stop service, equality in the level of service, and is a single seamless services. To support the implementation of integrated intermodal transport it is necessary to integrate network services, and network transport infrastructure. The purpose of this study was to develop criteria are integrated intermodal transportation at the airport, and the methods of analysis that will be used is the method of AHP (Analysis Process Hierarcy). The analysis of the results obtained CR (Consistent Ratio) 0.053404184 ≤ 0.10 were acceptable and consistent of each element criteria to be developed most major airports are the aspects: 1) Network Infrastructure, 2) Network services; 3) Services and other criteria that need to be developed is the intermodal integration of performance criteria, the criteria of regulatory integration Services, and operational criteria.ABSTRAKTransportasi udara merupakan salah satu moda transportasi yang memberikan manfaat besar seperti jangkauan yang luas, waktu tempuh yang relatif singkat, tarif yang terjangkau oleh masyarakat serta aman dan nyaman. Dalam rangka meningkatkan pelayanan penumpang angkutan udara dilakukan antara lain melalui pengembangan sistem transportasi udara di Indonesia yang diarahkan kepada terwujudnya keterpaduan pelayanan angkutan udara dengan berbagai moda transportasi sehingga dapat mewujudkan keterpaduan transportasi antarmoda. Penyelenggaraan transportasi antarmoda adalah untuk mewujudkan pelayanan penumpang yang berkesinambungan, one stop service, kesetaraan dalam level of service, dan bersifat single seamless services. Untuk mendukung keterpaduan penyelenggaraan angkutan antarmoda maka diperlukan keterpaduan jaringan pelayanan, dan jaringan prasarana transportasi. Tujuan dari penelitian ini adalah untuk menyusun kriteria keterpaduan transportasi antarmoda di bandar udara, dan metode analisis yang digunakan adalah metode AHP (Analysis Hierarcy Process). Dari hasil analisis diperoleh CR (consisten ratio) 0.053404184 ≤ 0,10 yang artinya diterima dan konsisten masing-masing elemen yang akan dikembangkan paling utama di bandar udara yaitu pada aspek: 1) Jaringan Prasarana; 2) Jaringan pelayanan; 3) Layanan, dengan kriteria yang perlu dikembangkan adalah kriteria kinerja keterpaduan antarmoda, kriteria regulasi keterpaduan pelayanan, dan kriteria operasional.